93.5k views
3 votes
Which expression is equivalent to (x^4/3 x^2/3)​

User Uss
by
5.9k points

1 Answer

4 votes

Answer:


x^(4)/(3)x^ (2)/(3)=x^{(4)/(3)+(2)/(3)}=x^{(16)/(12)+(8)/(12)}=x^(24)/(12)=x^2

Explanation:

The expression
x^(4)/(3)x^ (2)/(3) can be reduced using the exponent rule for multiplying same bases - add the exponents. Since the are fractions, find a common denominator - 12.


x^(4)/(3)x^ (2)/(3)=x^{(4)/(3)+(2)/(3)}=x^{(16)/(12)+(8)/(12)}=x^(24)/(12)=x^2

User Xpusostomos
by
5.7k points